Assessing Post-Surgery Pain and Recuperation in Laparoscopic Procedure Patients - Dr. Venkata Abhinay Sakam , Dr. Saravanan PS, Dr. Ravi R, Dr. Ganesh Kumar S (Cuestiones de Fisioterapia, 2025)
Background: This research seeks to assess post-surgery pain and recuperation in individuals who undergo laparoscopic procedures for abdominal discomfort. Methodology: A total of 200 patients participating in laparoscopic surgeries for various abdominal pain conditions were included in this forward-looking study was conducted at Meenakshi Medical College Hospital and Research Institute, Kanchipuram, between January and July 2024. Post-surgery pain was evaluated using a visual analog scale (VAS) every 6 hours during the initial 24-hour period. Recovery metrics, including the time taken to start walking, restoration of intestinal function, and duration of hospital stay, were documented and examined.